Comparison of Three Modalities of Feeding in Preterm Infants ≤32 Weeks and ≤1,250 G: A Randomized Controlled Trial - Kumar, Vijay; Thakur, Anup; Garg, Pankaj; Kler, Neelam (American Journal of Perinatology, 2023)
Objective Early establishment of enteral feeds is desirable in very preterm infants, but it may be associated with feeding intolerance. Several feeding methods have been studied with no strong evidence to suggest the preferred feeding method to establish early full enteral feeds. We studied three modalities of feeding in preterm infants ≤32 weeks and ≤1,250 g: continuous infusion (CI), intermittent bolus by infusion (IBI), and intermittent bolus by gravity (IBG) for their effect on time to reach full enteral feeds of 180 mL/kg/d.Study Design We randomized 146 infants, 49 infants in each CI and IBI group and 48 infants in the IBG group. In the CI group, feeds were delivered by an infusion pump continuously over 24 hours. In the IBI group, feeds were given every 2 hours and infused over 15 minutes by an infusion pump. In the IBG group, feeds were delivered by gravity over 10 to 30 minutes. The intervention was continued till infants reached direct breast/cup feeds.Results The mean (standard deviation) gestation in CI, IBI, and IBG groups were 28.4 (2.2), 28.5(1.9), and 28.6 (1.8) weeks, respectively. The time to reach full feeds in CI, IBI, and IBG were not significantly different (median [interquartile range]: 13 [10–16], 11.5 [9–17], and 13 [9.5–14.2] d, respectively, p = 0.71). The proportions of infants who developed feeding intolerance in CI, IBI, and IBG were similar (n [%]: 21 [51.2%], 20 [52.6%], and 22 [64.7%], respectively, p = 0.45). There was no difference in necrotizing enterocolitis ≥2 (p = 0.80), bronchopulmonary dysplasia (p = 0.86), intraventricular hemorrhage ≥2 (p = 0.35), patent ductus arteriosus requiring treatment (p = 0.44), retinopathy of prematurity requiring treatment (p = 0.51), and growth parameters at discharge.Conclusion In preterm infants, ≤32 weeks of gestation and birth weight ≤1,250 g, there was no difference in time to reach full enteral feeds in the three modalities of feeding. This study is registered with Clinical Trials Registry India (CTRI) and the registration number is CTRI/2017/06/008792.Key Points
Keywords: feeding intolerance; growth velocity; very low birth weight infants; feeding methods